Study on the Flow Dynamics of Nitrogen and Hydrogen Gases in a Monolithic Microchannel - Panneerchelvam, Hemala (IRC, 2016)
The current production of ammonia (NH3) through the synthesis of nitrogen (N2) and hydrogen (H2) gases requires the utilization of high pressure and high temperature system, which poses not only high risk on the safety of the operation, but also produces less ammonia yield. This process that is widely known in chemical industry as Haber-Bosh process has been carried out since the early 20th century, and is very energy intensive in an extreme production conditions. In order to reduce the operational risk, lowering the energy of operation and concurrently increases ammonia yield, a new inventive method is proposed by performing the synthesis inside a microchannel at ambient conditions.